SURVEY OF PHYSICAL FITNESS LEVEL OF GRADE XI STUDENTS OF SMA TARUNA PBD MEDAN IN THE 2024 – 2025 ACADEMIC YEAR - Atika Rahma Zulfi; Chairad, Muhammad; Nasution, Usman; ambri damanik, Saipul; Aulia, Rahma; Harahap, Nurkholilah; Iwan Saputra (Universitas Negeri Medan, 2025)
Physical fitness is an important aspect of every individual's physical condition because optimal physical fitness facilitates daily activities with ease and energy. Similarly, for students, good physical fitness significantly helps them study at school without experiencing lethargy or fatigue, both inside and outside the classroom. This study aims to evaluate the physical fitness level of high school students in Medan City. This study was conducted at Taruna PBD Medan Senior High School, with a sample size of 20 students. The research method used was descriptive quantitative. Based on data analysis, it was found that the percentage of physical fitness levels of 11th grade students at Taruna PBD Medan Senior High School was as follows: 9 students (45%) were included in the